An Ubuntu approach to disability and inclusive development for women with disabilities - Theresa Lorenzo; Maximus M. Sefotho (African Journal of Disability)
Background: Vicious cycles of disability and poverty isolate disabled women, making it difficult for them to meet their own and their family’s human needs. Their exclusion and deprivations may be bridged through inclusive development processes. The article presents an Afro-centric approach to inclusive development that speaks to experiences of disabled women who lived in informal settlements in the Cape Town metropole, South Africa that also has relevance for marginalised and oppressed communities in the Global North.